A apropriação das tecnologias da informação e comunicação por jovens e adultos não alfabetizados: um direito humano a ser garantido - as diretrizes da UNESCO - Franco, Mônica Gardelli (2009)
This research started from the finding of lack of public policies that would provide for the appropriation of information and communication technologies to promote the literacy of young people and adult populations as inalienable rights of human beings. Considering the importance of the role of UNESCO regarding the proposal of strategies, and in monitoring and evaluation of public policies for education performance, this research had the objective of extracting guidelines from its official documents for the drafting, the consolidation and improvement of public policies that would require the integration of communication technologies and information on proposals for literacy of young people and adults. The experience that led to the research practices and that have opened the problem of the thesis was the MOVA-digital, held in São Paulo s Municipal Department of Education, between 2001-2002. The analysis was performed based on two documents - ICT to develop Literacy and ICT in Education Toolkit for Policy Makers, Planners and Practitioners. The analysis of the documents took as a principle the ownership of technology as a human right and made reference to concepts disponível theoretical principles that argue for the appropriation of technologies and human development - concept represented by Álvaro Vieira Pinto, Manuel Castells and Nicolau Sevcenko; by the concept of literacy as a transformative and emancipatory practice - designed by Paulo Freire; and by development as a form of freedom - advocated by Amartya Sen and Jeffrey Sachs. The results indicate that the guidelines that subsidize the development of public policies presented by UNESCO consider aspects related to ensuring access and distribution, the regulation of rights, promotion of conditions of technology ownership, the replicability and sustainability of programs, as well as evaluation and monitoring, provisioning of resources for implementation, team building and professionals showing alternatives on possible solutions to this challenge to humanity. They have, however, revealed some important gaps in relation to actions for the proactive use of technology in favor of a movement of change and awareness for intervention in economic, political and human realities. It was concluded that public policies that require the integration of technology in promoting literacy and facing conditions of illiteracy should be central in the propositions of a high-level of education plan for a nation where the guarantee of freedom, autonomy and the exercise full citizenship for all could achieve its social, cultural, economic and human wants